2022
DOI: 10.22159/ijpps.2022v14i6.44548
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Admet Studies of Ethanone, 1-(2-Hydroxy-5-Methyl Phenyl) for Anti-Microbial Properties

Abstract: Objective: Ethanone 1-(2-hydroxy-5-methyl phenyl) found in the aerial parts of Rhizophora mucronate, Epiphyllum oxypetalum haw and dried ripened seed extracts of coffee. It has reported anti-microbial properties based on the literature. The objective of the present study is to find the binding efficacy of the compound with proteins in staphylococcus aureus and to report the ADMET properties of the compound. Methods: Rigid docking technique was used for finding the affinities.3D structures of the six proteins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Molecular docking analysis is conducted by using a calculation approach to measure the interaction between protein to small molecule. The analysis could be used to identify the inhibition ability of small molecules [14]. The utilization of the volatile compound of Pogostemon cablin Benth as an inhibitor candidate of SARS-CoV-2 glycoprotein showed that only five volatile compounds had lower binding affinity as compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking analysis is conducted by using a calculation approach to measure the interaction between protein to small molecule. The analysis could be used to identify the inhibition ability of small molecules [14]. The utilization of the volatile compound of Pogostemon cablin Benth as an inhibitor candidate of SARS-CoV-2 glycoprotein showed that only five volatile compounds had lower binding affinity as compared to the control.…”
Section: Resultsmentioning
confidence: 99%